2013
DOI: 10.1002/wrcr.20396
|View full text |Cite
|
Sign up to set email alerts
|

Combining fixed- and moving-vessel acoustic Doppler current profiler measurements for improved characterization of the mean flow in a natural river

Abstract: [1] A methodology is presented to quantify the mean flow field in a natural river with a boat-mounted acoustic Doppler current profiler (ADCP). Moving-vessel (MV) and fixedvessel (FV) survey procedures are used in a complementary fashion to provide an improved representation of mean three-dimensional velocity profiles along a cross section. Mean velocity profiles determined with FV measurements are rotated to a stream-fitted orthogonal coordinate system. The orientation of the coordinate system is established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
(68 reference statements)
0
11
0
Order By: Relevance
“…They did not determine how many transects would be required to give an accurate representation of the spatial distribution of the mean flow. Petrie et al [16] analyzed transects, so the spatial distribution that they refer to is along a cross-section, rather than areal or in 3D. Nevertheless, the zig-zag pattern employed in the present study, spatially averaged into a 3D matrix, replicates an averaged series of transect measurements that, in the real world, are rarely spatially concordant.…”
Section: Feasibility Of Representing 3d Flow In 3d Spacementioning
confidence: 83%
See 2 more Smart Citations
“…They did not determine how many transects would be required to give an accurate representation of the spatial distribution of the mean flow. Petrie et al [16] analyzed transects, so the spatial distribution that they refer to is along a cross-section, rather than areal or in 3D. Nevertheless, the zig-zag pattern employed in the present study, spatially averaged into a 3D matrix, replicates an averaged series of transect measurements that, in the real world, are rarely spatially concordant.…”
Section: Feasibility Of Representing 3d Flow In 3d Spacementioning
confidence: 83%
“…This assumption of constant flow is the same in discharge measurements using ADCP, even though, in the case of a single transect, the time-integration is smaller. Petrie et al [16] found the number of transect measurements to control the accuracy with which moving vessel ADCP measurements are able to model the spatial distribution of flow, while noting that the time-averaged flow velocities obtained from fixed-vessel measurements could not be reproduced by four spatially interpolated transects. They did not determine how many transects would be required to give an accurate representation of the spatial distribution of the mean flow.…”
Section: Feasibility Of Representing 3d Flow In 3d Spacementioning
confidence: 99%
See 1 more Smart Citation
“…Considerations when applying the log law to field measurements include that the measured velocity profile may not capture the logarithmic region or a logarithmic region may not exist. Field (Petrie et al , , ) and laboratory (Diplas, ) measurements have confirmed deviations from the log law as elevation increases. To address this limitation, the extent of the logarithmic region can be visually determined using a semi‐logarithmic plot of the velocity profile.…”
Section: The Logarithmic Law Of the Wallmentioning
confidence: 88%
“…Venditti et al, 2014;Alvarez et al, 2017;Tomas et al, 2018), deltas (e.g. Szupiany et al, 2007;Jackson et al, 2008) and also to process these data carefully, (Muste et al, 2004;Rennie and Church, 2010;Tsubaki et al, 2012;Parsons et al, 2013;Petrie et al, 2013). García et al, 2007).…”
Section: Introductionmentioning
confidence: 99%